The European Green Deal: What Prospects for Governing Climate Change With Policy Monitoring? - Schoenefeld, Jonas J. (2021)
The European Green Deal (EGD) puts forward and engages with review mechanisms, such as the European Semester and policy monitoring, to ensure progress towards the long-term climate targets in a turbulent policy environment. Soft-governance mechanisms through policy monitoring have been long in the making, but their design, effects, and politics remain surprisingly under-researched. While some scholars have stressed their importance to climate governance, others have highlighted the difficulties in implementing robust policy monitoring systems, suggesting that they are neither self-implementing nor apolitical. This article advances knowledge on climate policy monitoring in the EU by proposing a new analytical framework to better understand past, present, and potential future policy monitoring efforts, especially in the context of the EGD. Drawing on Lasswell (1965), it unpacks the politics of policy monitoring by analysing who monitors, what, why, when, and with what effect(s). The article discusses each element of the framework with a view to three key climate policy monitoring efforts in the EU which are particularly relevant for the EGD, namely those emerging from the Energy Efficiency Directive, the Renewable Energy Directive, and the Monitoring Mechanism Regulation (now included in the Energy Union Governance Regulation), as well as related processes for illustration. Doing so reveals that the policy monitoring regimes were set up differently in each case, that definitions of the subject of monitoring (i.e., public policies) either differ or remain elusive, and that the corresponding political and policy impact of monitoring varies. The article concludes by reflecting on the implications of the findings for governing climate change by means of monitoring through the emerging EGD.